Les pouvoirs de l'exécuteur testamentaire : étendue maximale et durée - Castelli, Mireille (Les Cahiers de droit, 1978)
A testator can increase or diminish the extent as well as the duration of the powers provided an executor by the Civil Code of Quebec. However, regardless of how positive the formula that he uses may be, he cannot grant absolute and arbitrary powers. That is true whether one considers the executor the agent of the deceased or of the legatees. In effect, it is the purpose of the administration of a testamentary estate which dictates the solution. Since that purpose is to carry out the will of the deceased, the first duty of the executor is to attempt to assure the legatee or the heir the largest possible patrimony. In any case, the executor would not be freed from the control which a request for his dismissal represents unless he should be a residuary legatee. A clause which would have that as its purpose would be considered null and void as contrary to public order and good morals. Moreover, the duration of the administration of an estate can never be prolonged once the administration has been completed even if the testator had foreseen an administration of a longer duration. The only difference the formula used by the testator could make (the possibility of prolounging longer than necessary the administation of the estate) would be to influence the burden of proof which, in one case, would fall on the executor and, in the other, on the heirs or legatees.